Antileishmanial activity of nanocurcumin. (February 2011) - Samim, Mohd; Naqvi, Saba; Arora, Indu; Ahmad, Farhan Jalees; Maitra, Amarnath
Background: Leishmaniasis is an endemic disease having a wide spectrum ranging from visceral, cutaneous and mucocutaneous forms caused by unicellular, obligate intracellular parasites of the monocyte––macrophage system. The aim of the present study was to develop an effective, nontoxic and biodegradable polymeric drug-delivery system encapsulating curcumin in its hydrophobic core for the treatment of visceral leishmaniasis.Results: We have reported a co-polymeric micelle of N -isopropyl acrylamide, vinyl pyrrolidone and acrylic acid in 85:10:5 M ratios through free radical polymerization. The characterization of curcumin-loaded nanoparticles (40––50 nm) was done by transmission electron microscopy, dynamic light scattering and spectroscopic methods such as NMR which ensures polymerization and formation of nanoparticles has been achieved. Nanocurcumin was evaluated as an antileishmanial agent through spleenomegaly and delayed-type hypersensitivity experiments.Conclusion: Nanocurcumin has shown significantly greater in vivo therapeutic efficacy than pentamidine and free curcumin in an animal model of visceral leishmaniasis. The use of nanocurcumin compared with conventional drugs and free curcumin may prove more feasible and provide a better approach towards treatment of leishmaniasis.